Polarimeter + Lidar–Derived Aerosol Particle Number Concentration - Schlosser, Joseph S.; Stamnes, Snorre; Burton, Sharon P.; Cairns, Brian; Crosbie, Ewan; Van Diedenhoven, Bastiaan; Diskin, Glenn; Dmitrovic, Sanja; Ferrare, Richard; Hair, Johnathan W.; Hostetler, Chris A.; Hu, Yongxiang; et al. (Frontiers in Remote Sensing, 2022)
In this study we propose a simple method to derive vertically-resolved aerosol particle number concentration (Na) using combined polarimetric and lidar remote sensing observations. This method relies on accurate polarimeter retrievals of the fne-mode column-averaged aerosol particle extinction cross-section and accurate lidar measurements of vertically-resolved aerosol particle extinction coeffcient such as those provided by multi-wavelength High Spectral Resolution Lidar. We compare the resulting lidar+polarimeter vertically-resolved Na product to in-situ Na data collected by airborne instruments during the NASA Aerosol Cloud meTeorology Interactions oVer the western ATlantic Experiment (ACTIVATE). Based on all 35 joint ACTIVATE fights in 2020, we fnd a total of 32 collocated in-situ and remote sensing profles that occur on 11 separate days, and which contain a total of 322 cloud-free vertically-resolved altitude bins of 150 m resolution. We demonstrate that the lidar+polarimeter Na agrees to within 106% for 90% of the 322 vertically-resolved points. We also demonstrate similar agreement to within 121% for the polarimeter-derived column-averaged Na. We fnd that the range-normalized mean absolute deviation (NMAD) for the polarimeter-derived column-averaged Na is 21% and the NMAD for the lidar+polarimeter-derived vertically-resolved Na is 16%. Taken together, these fndings suggest that the error in the polarimeter-only column-averaged Na and the lidar+polarimeter vertically-resolved Na are of similar magnitude and represent a signifcant improvement upon current remote sensing estimates of Na.